2015
DOI: 10.1136/inp.g6815
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis and management of corneal ulceration in horses, part 2

Abstract: This article considers the various aetiologies of corneal ulceration in horses, along with treatments and prognoses. It is the second in a two-part series in In Practice. The first article (Hartley 2014) focused on corneal anatomy and healing, ulcer classification and the diagnostic approach to a painful eye, emphasising the importance of appropriate and timely treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Escherichia coli are gram‐negative bacteria from the family Enterobacteriaceae and are not known as significant pathogens of the equine cornea 21 . They are, however, part of the normal ocular flora of horses as well as their environment, and can therefore be isolated from an ulcerated equine eye if the injury to the cornea occurred following trauma with faeces or a foreign body contaminated with E. coli 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Escherichia coli are gram‐negative bacteria from the family Enterobacteriaceae and are not known as significant pathogens of the equine cornea 21 . They are, however, part of the normal ocular flora of horses as well as their environment, and can therefore be isolated from an ulcerated equine eye if the injury to the cornea occurred following trauma with faeces or a foreign body contaminated with E. coli 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli are gram‐negative bacteria from the family Enterobacteriaceae and are not known as significant pathogens of the equine cornea 21 . They are, however, part of the normal ocular flora of horses as well as their environment, and can therefore be isolated from an ulcerated equine eye if the injury to the cornea occurred following trauma with faeces or a foreign body contaminated with E. coli 21 . This could have occurred to the patient with a positive E. coli result in this study, as it was referred to UVTHC promptly after being found in the early morning with acute eye lesions which were absent the night before.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal ulcer is a common and potentially serious condition in horses. Damage to the cornea, resulting in loss of epithelial cells with exposed corneal stroma, creates an ulcer on the corneal surface [1]. Squinting (blepharospasm) or keeping an eye shut and tearing (epiphora) are often the first signs owners will notice in pets with corneal ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescein stain uptake in the ulcerated region confirms the diagnosis of an ulcer. Categorization of the ulcer is based on a combination of clinical signs and visual inspection of the eye [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation